Damage evolution and fracture of ceramic coating systems in circle plate bending tests: Experimental observation and modeling. Issue 6 (15th April 2020) - Liu, H.Y.; Wei, Y.G.; Liang, L.H.; Liu, X.H.; Wang, Y.B.; Long, H.
Abstract: The coating thickness-dependent damage and fracture of ceramic coating systems were investigated systematically by using circle plate bending tests based on a scanning electron microscope. Through experimental observations and measurements, results demonstrated that the damage of coating layer appeared because of effects of both radial and circumferential moments for thin coating cases, and because of main circumferential moment effect for thick ones. A circle plate bending damage model for the coating layer was presented to describe coating layer damage evolution and fracture. Via the model, one can effectively predict the failure phenomena of coating layer under the circle plate bending, which were consistent with experimental observations. In addition, modeling results of the relationships between critical external loads and damage zone sizes for coating layer were also consistent with experimental measurements. The damage was found to have a catastrophic characteristic near the failure point based on the mathematic damage model.